2018
DOI: 10.1002/oby.22331
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐Loss Outcomes from a Pilot Study of African Dance in Older African Americans

Abstract: Objective: Obesity is a risk factor for both cognitive and physical impairment in late adulthood. Though the rates of obesity are high in many groups, older African Americans are disproportionately affected. Here, we conducted a randomized pilot intervention of African Dance with 28 African American older adults with obesity (Mean age = 68.4 ±5.1 years; Mean BMI = 33.4 ± 6.2). The goal of the study was to evaluate the physiological outcomes of a culturally sensitive exercise intervention, and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Of 57,721 unique records, 109 articles of 54 studies were included in the evidence map as they provided information on outcomes assessed (Figure 1 and Table S4). 34–87 The unique accession numbers from all database searches are available upon request.…”
Section: Resultsmentioning
confidence: 99%
“…Of 57,721 unique records, 109 articles of 54 studies were included in the evidence map as they provided information on outcomes assessed (Figure 1 and Table S4). 34–87 The unique accession numbers from all database searches are available upon request.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have sought to increase PA in older African Americans (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Two of these studies utilized pedometers to assess PA (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a small study demonstrated that aerobic training has a blunted effect on insulin resistance in African American compared with non-Hispanic White adults (12), and another study showed that cardiorespiratory fitness improvements among African American women attenuate at a lower dose of exercise compared with non-Hispanic White women (13). Several studies have assessed the effect of a PA intervention specifically in older African Americans (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and many resulted in increases in PA. Many of these studies can be strengthened by utilizing community-engaged methods and by incorporating device-assessed, compared with selfreported, PA.…”
mentioning
confidence: 99%
“…Statistically significant positive correlations were identified among physical activity, perceived health competence, duration of diabetes, and social well-being, indicating the potential of physical activity to decrease the risks associated with chronic illnesses, particularly in AA women [14]. Another study found that 6-month physical activity programs were effective in managing numerous physical and neurocognitive complaints in middle-aged and elderly patients [15].…”
Section: Physical Performance Issuesmentioning
confidence: 96%